Criteria for the transition to adulthood, developmental features of emerging adulthood, and views of the future among Greek studying youth - Galanaki, Evangelia; Sophie Leontopoulou (Europe's Journal of Psychology, 2017)
This study investigated emerging adulthood and transition to adulthood in Greece, a highly underresearched issue in this country. Participants were 784 university students aged 17.5-27.5 years. Criteria for the transition to adulthood, developmental features of emerging adulthood, perceived adult status, views of the future (optimism), and sociodemographic variables were assessed. The results support the existence of emerging adulthood as a distinct life period in Greece. More than two thirds of the sample were self-perceived emerging adults. Most prevalent criteria were Norm compliance and Family capacities. Developmental features of emerging adulthood ranked high, especially Identity exploration, Experimentation/possibilities, and Feeling “in-between”. Statistically significant variations emerged as a function of gender, age, living arrangement, job experience, and perceived adult status. Views of the future were cautiously optimistic. Similarities with existing data and differences related to the specific characteristics of the Southern European context are discussed.